Panchayati Raj - "Mathur, Kuldeep" (New Delhi, 2013)
This volume is a comprehensive account of Panchayati Raj institutions in India since the 73rd Constitutional Amendment mandated them in the year 1993. While local governance is not new to India, the present system of Panchayats was created and developed in the midst of the post-1991 reforms and 'liberalization' of the state-centric political economy. Civil society and market were to acquire greater roles in the delivery of public services at the local level, and decentralization of governance institutions was initiated. This Short Introduction presents a balanced and complete picture of the philosophy, objectives, evolution, successes, and failures of these institutions in the last two decades. Contextualizing the Panchayats in their larger institutional, functional, and ideological framework, this book outlines the Gandhian legacy; the socio-political trajectory of the Constitutional mandate; the debates and realities of political and financial autonomy of Panchayats; and the workings of affirmative action through Panchayats. It also provides significant pointers to the critically important roles the Panchayats are to play in the future.
Keywords: Panchayat